Salicylic acid: new pathways arising? - Müller, Jonas; Scheuring, David (Frontiers in Plant Science, 2025)
While the role of salicylic acid (SA) for plant immunity has been investigated for decades, its function in regulating plant growth and development has only come into focus recently. Several studies indicate that SA – auxin crosstalk plays an important role in mediating SA-induced effects. However, not all findings can be explained by this crosstalk alone and SA-specific effects on intracellular organization have been reported such as inhibition of endocytosis and changes of vacuolar pH and morphology. Notably, several SA-related functions seem to be independent of the SA receptors Nonexpressor of Pathogenesis-Related genes (NPRs). This review summarizes the effects of SA on intracellular organization and predicts the existence of as yet unknown signaling pathways to explain the current findings. We provide a short general introduction including SA biosynthesis and SA signaling and address how NPR-independent intracellular changes necessitate specific signaling to regulate growth and development.